Evaluation of technological and bakery properties of winter rye in dependence on predecessor in adaptive-landscape crop farming - L. M. Kozlova; A. V. Denisova; I. V. Lyskova; S. N. Zhuk (Аграрная наука Евро-Северо-Востока, 2017)
Results of perennial studies on influence of predecessors on grain quality parameters of winter rye Kirovskaya 89 and Falenskaya 4 are presented in the article. Winter rye was sowed after such kinds of fallow as pure, manure, green manure (lupine, melilot, red clover, annual grasses), occupied (field pea + oat; radish + vetch + oat; clover). It was established that predecessor could influence on grain quality of winter rye due to its impact on agro-physical, biological properties of soil, and phyto-sanitary state of sowings. Test weight of grain varied by years and by predecessors in Kirovskaya 89 from 564 up to 707 g/l; in Falenskaya 4 - from 650 up to 710 g/l. At the average for years of investigations, both varieties formed high-test weight grain according to State Standard. Grain of variety Kirovskaya 89 belongs to II class of quality on a base of parameter “falling numbef’ at any predecessor - its grain does not demand subgrading (bread of good quality). Variety Falenskaya 4 forms grain of I class in majority of years and was characterized as improver for subgrading for grain with low qualities. 1000 grain mass in variety Kirovskaya 89 was significantly higher at green manure fallow, in variety Falenskaya 4 - at pure fallow. Protein content was low than 11.5% at any predecessor and type of fallow that does not lowered bakery properties of flour. Total bakery value of variety Kirovskaya 89 at pure fallow was 3.09 points, increased at green manure, and occupied fallows up to 3.51.3.57 points.